Socio‐economic disadvantage is associated with heavier drinking in high but not middle‐income countries participating in the International Alcohol Control Study. (30th April 2018) - Huckle, Taisia; Romeo, Jose S.; Wall, Martin; Callinan, Sarah; Holmes, John; Meier, Petra; Mackintosh, Anne‐Maree; Piazza, Marina; Chaiyasong, Surasak; Cuong, Pham Viet; Casswell, Sally
Abstract: Introduction and Aims: To investigate if socio‐economic disadvantage, at the individual‐ and country‐level, is associated with heavier drinking in some middle‐ and high‐income countries. Design and Methods: Surveys of drinkers were undertaken in some high‐ and middle‐income countries. Participating countries were Australia, England, New Zealand, Scotland (high‐income) and Peru, Thailand and Vietnam (middle‐income). Disadvantage at the country‐level was defined as per World Bank (categorised as middle‐or high‐income); individual‐level measures were (i) years of education and (ii) whether and individual was under or over the poverty line in each country. Measures of heavier drinking were (i) proportion of drinkers that consumed 8+ drinks and (ii) three drinking risk groups (lower, increasing and higher). Multi‐level logistic regression models were used. Results: Individual‐level measures of disadvantage, lower education and living in poverty, were associated with heavier drinking, consuming 8+ drinks on a typical occasion or drinking at the higher risk level, when all countries were considered together. Drinkers in the middle‐income countries had a higher probability of consuming 8+ drinks on a typical occasion relative to drinkers in the high‐income countries. Interactions between country‐level income and individual‐level disadvantage were undertaken: disadvantaged drinkers in the middle‐income countries were less likely to be heavier drinkers relative to those with less disadvantage in the high‐income countries. Discussion and Conclusions: Associations between socio‐economic disadvantage and heavier drinking vary depending on country‐level income. These findings highlight the value of exploring cross‐country differences in heavier drinking and disadvantage and the importance of including country‐level measurements to better elucidate relationships.